Bruce Lee en Chile: ironía y parodia en Fuenzalida de Nona Fernández. Issue 1 (2nd January 2017) - Maier, Gonzalo
ABSTRACT: This article analyzes the use of irony and the parody of Bruce Lee in Fuenzalida (2012 ), a novel by the Chilean author Nona Fernández. Through a close reading of the text, I endeavor to show how the novel parodies Enter the Dragon, the most famous of Bruce Lee's films. In this way, the narrator imagines an alternative biography of her father, as if he never voluntarily left her for another family, but rather was forced by the dictatorship to abandon her. The narrator's memories do not distinguish between reality and imagination as she creates a fantasy in the form of bruceploitation films, in which her father fought like a martial arts star against the greatest enemies of the Chilean dictatorship. Thus, irony and parody allow us to understand how martial arts films of the 1970s can be used to elaborate both a private and a political mourning.